2022
DOI: 10.3389/fimmu.2022.921085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Exercise Training on Body Composition and Inflammatory Cytokine Levels in Overweight and Obese Individuals: A Systematic Review and Network Meta-Analysis

Abstract: ObjectiveThis study aimed to compare and rank the effectiveness of aerobic exercise (AE), resistance training (RT), combined aerobic and resistance training (CT), and high-intensity interval training (HIIT) on body composition and inflammatory cytokine levels in overweight and obese individuals by using network meta-analysis (NMA).MethodsWe searched the PubMed, Cochrane, Embase, Web of Science, and EBSCO databases to identify randomized controlled trials investigating the effects of exercise training on inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 95 publications
(110 reference statements)
0
17
0
Order By: Relevance
“…This finding is probably reflected in the increase in muscle mass, a tissue that holds a large amount of ICW, resulting in better electrical conductivity and, thus, a concomitant increase in PhA. Others cellular mechanisms might be involved if we considering that exercise results in a greater reduction in CRP, IL-6, and TNF-a when accompanied by a reduction in BMI or FM% in overweight/obese individuals [ 80 ]. Furthermore, studies have shown that PhA increases after a training period or is higher in active subjects compared to less active ones, suggesting that many of the exercise-induced systemic adaptations can impact cell integrity and functionality [ 78 , 81 , 82 ].…”
Section: Introductionmentioning
confidence: 99%
“…This finding is probably reflected in the increase in muscle mass, a tissue that holds a large amount of ICW, resulting in better electrical conductivity and, thus, a concomitant increase in PhA. Others cellular mechanisms might be involved if we considering that exercise results in a greater reduction in CRP, IL-6, and TNF-a when accompanied by a reduction in BMI or FM% in overweight/obese individuals [ 80 ]. Furthermore, studies have shown that PhA increases after a training period or is higher in active subjects compared to less active ones, suggesting that many of the exercise-induced systemic adaptations can impact cell integrity and functionality [ 78 , 81 , 82 ].…”
Section: Introductionmentioning
confidence: 99%
“…Combined exercise programs (AE + RT) have recently emerged as one of the most efficient strategies not only to improve body composition 28,50 but also as the most effective training mode for improving metabolic inflammatory markers. 30,51,52 The current NMA showed that AE 53 In addition, several meta-analyses have found that AE + RT is the best exercise mode for improving inflammation in obesity. 30,53,54 Therefore, AE + RT is recommended as the most appropriate treatment for the simultaneous improvement of VAT, inflammation, and muscle mass and strength.…”
Section: Effect Of Exercise On Primary Outcomesmentioning
confidence: 88%
“…Increased muscle and bone mass and decreased VAT were observed only with the AE + RT regimen 53 . In addition, several meta‐analyses have found that AE + RT is the best exercise mode for improving inflammation in obesity 30,53,54 . Therefore, AE + RT is recommended as the most appropriate treatment for the simultaneous improvement of VAT, inflammation, and muscle mass and strength.…”
Section: Discussionmentioning
confidence: 99%
“…64 In addition, regular exercise, optimally a combination of endurance other important obesity-related health parameters. [65][66][67][68] However, it should be considered that many people with obesity show orthopaedic impairments that preclude a high level of physical activity. In addition, there is evidence that habitual physical activity is to a great extent biologically determined and remains relatively stable at an individual level even after relevant changes in body weight.…”
Section: Implications For Anti-obesity Therapy 91 | Strengthening Top...mentioning
confidence: 99%
“…While it has been shown to be not very effective in reducing body weight, it is well documented that increasing physical activity helps to maintain body weight at a lower level 64 . In addition, regular exercise, optimally a combination of endurance and resistance training, clearly improves body composition by increasing muscle mass and decreasing fat mass and by ameliorating many other important obesity‐related health parameters 65–68 . However, it should be considered that many people with obesity show orthopaedic impairments that preclude a high level of physical activity.…”
Section: Implications For Anti‐obesity Therapymentioning
confidence: 99%